Engineering-geological and geotechnical investigations for risk assessment of the University Olympic Village in Izmir (Turkey) - Kincal, Cem; Koca, Mehmet; Yilmaz, H. Recep; Akgün, Mustafa; Özyalin, Şenol; Eskişar, Tuğba; Akçiğ, Zafer; van Loon, A.J. (Tom) (Geologos, 2010)
The Metropolitan Municipality of Izmir (Turkey) designated a steeply inclined area for the construction of buildings to house the participants of the Izmir University Olympic Games. Before the construction activities could start, engineering geological and geotechnical investigations had to be carried out in order to establish which zones in the area were suitable for safe constructions. Seismic studies, borings and laboratory tests yielded the data, which were used for preparing five hazard maps in a GIS environment. The construction activities based on the results of this complex investigation appeared successful. The engineering geological investigations included geotechnical measurements on core samples obtained from the boreholes (core drilling) and laboratory testing. The rock-quality designation (RQD%) values of the rock units were determined and used in the rock-mass classification (rock-mass rating method) as an input parameter and in the calculation of the bearing capacity of the various rock units. Geophysical surveys were carried out to determine the seismic velocity of the rocks at the site. A short overview is provided of the main problems that had to be dealt with, and of the successive steps taken to solve the engineering-geological problems. Determination of these problems is necessary for adequate land-use planning and construction activities.